Nephrolithiasis Associated with Normocalcemic or Hypercalcemic Primary Hyperparathyroidism: An Update on Medical Management - Simone Brardi; Ennio Duranti (Archives of Renal Diseases and Management - Peertechz Publications, 2016)
Primary hyperparathyroidism (PHPT) is a disease involving a broad range of alterations of calcium homeostasis, sustained by parathyroid hormone (PTH) levels that are clearly abnormal. The anomalies directly associated with hyperparathyroidism are nephrolithiasis and fibrocystic bone disease. Since PHPT resolves when abnormal parathyroid tissue is removed, surgery is clearly the only definitive approach to this type of hyperparathyroidism. However there are large subgroups of patients for whom medical therapy should be considered instead of surgery. Pharmacological therapy consists largely of biphosphonates, or calciomimetics such as cinacalcet. Recent preliminary data suggests however that cinacalcet could also be effective in the specific group of patients with primary hyperparathyroidism associated  with  nephrolithiasis.  Finally,  since  cinacalcet  reduces  calcemia  in  most  PHPT  patients without  improving  bone  mass,  whereas  biphosphonates  and  especially  alendronate  improve  bone mass, it could make sense to combine the two drugs in PHPT patients with concomitant bone loss and possibly nephrolithiasis who cannot or do not wish to undergo surgery.